Kepatuhan Konsumsi Tablet Tambah Darah terhadap Anemia Remaja Putri - Saleh, Ummi Kaltsum S.; Bakoil, Mareta B. (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2021)
The consumption iron tablets for adolescent girls is one indicator of improving community nutrition. Research data in various regions in Indonesia shows the prevalence of anemia in adolescents girls ranges from 32.4% to 61%. The main causes of nutritional anemia in adolescents girls are due to lack of nutrient intake through food, iron loss in adolescents girls with more menstrual patterns and longer periods. Another reason is adolescents girls often maintain their appearance, the desire to stay slim or thin so that they go on a diet and eat less. The purpose of this study was to determine the compliance of iron tablet consumption on the incidence of anemia in adolescents girls. The research design was analytical observation with a cross sectional study approach for 12 weeks.. The number of sample in this study are 104 respondents (total sampling). The results showed that most of the adolescents ages 12-18 years (86.4%), 83 (79.8%) of the adolescents girls were anemia before consumption iron tablets. After consumption iron tablets for 12 weeks and mentoring as many as 69 people (66.3%) were obedient in consuming iron tablets and most of the adolescents girls (81.2%) weren’t anemia after consuming iron tablets for 12 weeks.